Iron metabolism and the role of HFE gene polymorphisms in Wilson disease - Pfeiffenberger, Jan; Gotthardt, Daniel; Herrmann, Thomas; Seeßle, Jessica; Merle, Uta; Schirmacher, Peter; Stremmel, Wolfgang; Weiss, Karl Heinz (Liver international, 2012)
Wilson disease (WD) is a rare inherited disorder of copper metabolism, which can lead to severe liver failure and to a variety of neuropsychiatric symptoms. Previous animal studies and case reports suggest that hepatic iron overload and alterations in iron processing are associated with WD. The aim of this study was the assessment of iron metabolism and of the frequency of the most common HFE gene polymorphisms in WD patients. Patients and methods Data from 143 patients with WD were analysed. Clinical presentation, liver function and iron metabolism parameters were recorded. Blood samples of the patients were analysed for HFE gene alterations (H63D; C282Y). Twenty-seven liver biopsies of these patients were studied with regard to iron content and fibrosis score. Results Contrary to previous reports of HFE gene polymorphisms in WD patients, in our cohort the allele frequencies (C282Y: 2.1%; H63D: 7.3%) were in line with frequencies obtained for general population. Male WD patients with decreased serum ceruloplasmin (Cp), showed increased serum ferritin levels. Hepatic iron content was normal in most cases. Discussion Male patients with very low Cp serum concentrations showed slightly elevated median serum ferritin concentrations, probably related to lack of ferroxidase acitivity. However, in consideration of absolute numbers of ferritin concentrations, these changes seem to be of minor clinical relevance.